THE STUDENTS’ DIFFICULTIES IN USING DEMONSTRATIVE PRONOUN - Muhammad Arief Paturusi (Universitas Muhammadiyah Makassar, 2016)
The objective of the research was to find out the Students’ Difficulties in Using Demonstrative Pronoun at the second year of SMP Aisyiyah Sungguminasa. The researcher applied descriptive quantitative approach as the method for analyzing the data. The researcher collected the data through objective test and questionnaire. The objective test was used to find out the students ability in using the demonstrative pronoun. The test formulated with 20 items multiple choice and a questionnaire was used to find out the students difficulties in using a demonstrative pronoun, the sample of this research was the second year students of SMP Aisyiyah Sungguminasa in academic year 2014/2015, the sample consisted of 26 students which were taken from the population, 26 students. The data obtained from the test were firstly tabulated, and then analyzed into the technique of percentage and mean analysis. The result of the research data showed that the ability of the second year students of SMP Aisyiyah Sungguminasa found difficulty in using Demonstrative Pronoun with the total mean score 41or classified as fair with the highest score was 60 and the lowest score is 1.6. The finding also showed that among the 26 students, there were 47.25% the students face difficulties in using Demonstrative pronoun “this” in sentences correctly. While there was 65.38% the students faced difficulties in using “that”. In using demonstrative pronoun “these” there were 93.26% the most error. And there was 44.61% the students faced difficulties in using demonstrative pronoun “those”. The researcher concluded that almost all of students got the difficulties in using the demonstrative pronoun. The difficulties were caused the students had less understanding about demonstrative pronoun because they never learned about it before.Keywords: Students’ Difficulties, Demonstrative Pronoun